201k views
14 votes
Which expression correctly sets up the quadratic formula with x^2+1=2x-3

1 Answer

6 votes

Given:

The quadratic equation is


x^2+1=2x-3

To find:

The expression that correctly sets up the quadratic formula with the given equation.

Solution:

We have,


x^2+1=2x-3


x^2+1-2x+3=0


x^2-2x+4=0

On comparing with
ax^2+bx+c=0, we get


a=1,b=-2,c=4

The quadratic formula is


x=(-b\pm √(b^2-4ac))/(2a)

Putting
a=1,b=-2,c=4, we get


x=(-(-2)\pm √((-2)^2-4(1)(4)))/(2(1))

Therefore, the required expression is
(-(-2)\pm √((-2)^2-4(1)(4)))/(2(1)).

User Rod Xavier
by
5.2k points